The Effect of Transformational Leadership and Intrinsic Motivation on Employee Performance with Work Discipline as an Intervening Variable on Employees in the Planning Field, the Field Distribution and Commerce and Management Fields Customers at PT PLN (Persero) UID North Sumatra - Arif Fahmi; Husni Muharram Ritonga (CV. Doki Course and Training, 2026)
This research seeks to explore how transformational leadership and intrinsic motivation impact employee performance, with work discipline serving as a mediating variable, among workers in the Planning, Distribution, and Commerce and Customer Management Divisions at PT PLN (Persero) UID North Sumatra. A quantitative methodology was employed via a survey approach. The entire workforce of 99 employees was included through a saturated sampling strategy. Data was gathered using a questionnaire, and the analysis was carried out using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The findings show that transformational leadership and intrinsic motivation positively and significantly influence both work discipline and employee performance. Additionally, work discipline has a positive and significant impact on employee performance and functions as a mediating factor in the connection between transformational leadership and intrinsic motivation concerning employee performance. These results support the idea that enhancing employee performance can be achieved through the application of transformational leadership and boosting intrinsic motivation, backed by effective work discipline.